MENGUNGKAP SISTEM PENGENDALIAN BELIEF SYSTEM PADA UNIVERSITAS YANG BERBASIS ENTREPRENEURSHIP: SEBUAH STUDI FENOMENOLOGI (Jurnal Manajemen dan Kewirausahaan, 2015)
The purpose of this study was to reveal the meaning of belief system from lecturer perspective in Universitas Ciputra. This research used Phenomenology to uncover phenomena. Two major data collections were indepth interview and participative observation. This research used source and method of triangulation. Based on informant experience, control systems meant social system which could influence subject to act comply with university regulation. This study found that creativity was very important for entrepreneurial organization.